2012
DOI: 10.1093/schbul/sbs087
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HLA Polymorphisms in Relation to Schizophrenia Risk and Infectious Exposure

Abstract: Background: Genome-wide association studies (GWAS) implicate single nucleotide polymorphisms (SNPs) on chromosome 6p21.3-22.1, the human leukocyte antigen (HLA) region, as common risk factors for schizophrenia (SZ). Other studies implicate viral and protozoan exposure. Our study tests chromosome 6p SNPs for effects on SZ risk with and without exposure. Method: GWASsignificant SNPs and ancestry-informative marker SNPs were analyzed among African American patients with SZ (n = 604) and controls (n = 404). Exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Following our systematic search 2866 studies were found, from which 50 studies were finally included (see flowchart in Fig. ) . Of these studies, four were unpublished (Hammer C, Ehrenreich H. 2014, personal communication, Torrey E. 2003, personal communication, Gallo C. 2005, personal communication, and Dickerson F. 2005, personal communication).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following our systematic search 2866 studies were found, from which 50 studies were finally included (see flowchart in Fig. ) . Of these studies, four were unpublished (Hammer C, Ehrenreich H. 2014, personal communication, Torrey E. 2003, personal communication, Gallo C. 2005, personal communication, and Dickerson F. 2005, personal communication).…”
Section: Resultsmentioning
confidence: 99%
“…Other authors set the cut‐off at the 75th or 90th percentile of seropositive control subjects to distinguish subjects with high titers . We calculated ORs using above‐mentioned studies and six studies that did not publish their serointensity rates (Torrey E. 2003, personal communication, Gallo C. 2005, personal communication), whereby we used the 75th and 90th percentile cut‐offs of the provided data.…”
Section: Resultsmentioning
confidence: 99%
“…Except for the APOE and TLR studies, viral shedding rates were not reported. Additional genetic loci within the extended HLA region on chromosome 6, aside from classical HLA class I and II, have also been shown to influence HSV severity, including an allelic variant at SNP rs3130297 genotype in the HLA class II region between the 3’ UTR of BTNL2 and the 5’ UTR of NOTCH4 (13). Several complement protein genes are also located in the HLA major histocompatibility complex (MHC) region.…”
Section: Discussionmentioning
confidence: 99%
“…Several functional allelic variants and single-nucleotide polymorphisms of genes encoding immune and inflammatory molecules have been associated with depression and schizophrenia, including those encoding the expression of inflammatory cytokines, major histocompatibility complex proteins, B and T cells, and inflammatory mediators such as cyclo-oxygenase2 (Bamne et al, 2012;Bosker et al, 2011;Bufalino et al, 2012;Raison and Miller, 2013; Schizophrenia Working Group of the Psychiatric Genomics, 2014). These findings have engendered speculation as to whether alleles that promote enhanced inflammatory cytokine secretion were evolutionarily advantageous and thus conserved (Raison and Miller, 2013).…”
Section: Gene Expression and Genetic Predispositionmentioning
confidence: 99%